Penggunaan Program Linier dengan Metode Simpleks untuk Mengoptimalkan Keuntungan Usaha Bolu - Palahudin, Palahudin; Firda Fauziah; Alfin Adam; Malya Savana Kurnia; Fatimah Azzahra; Ibnu Muhammad Sabili (Lembaga Pengembangan Kinerja Dosen, 2025)
Optimal resource management is a key factor in enhancing efficiency and profitability in a business. The simplex method, as one of the approaches in linear programming, provides an analytical tool to solve optimization problems with specific constraints. This research aims to apply the simplex method to optimize business profits in a case study. The data used includes production capacity, costs, and market demand. Through the application of this method, an optimal solution was obtained, showing the combination of products and resource allocation that generates maximum profit. The findings demonstrate that the simplex method is highly useful in supporting strategic actions, particularly in efficient resource allocation. Thus, this method can serve as a reference for business practitioners in designing strategies to sustainably increase profitability. Additionally, it is expected that the results of this study can actively contribute to supporting the development of effective and sustainable business strategies.